Feasibility of Oil Palm Agroforestry System: Evaluating the Application of Oil Palm Ash for Enhancing Cherry Tomato (Solanum Lycopersicum. Var. Nancy Rz) Production Using Brackish Water. - Bassey, Ime Joseph (AUC Knowledge Fountain, 2024)
Monoculture systems of oil palm production are ravaging the world’s tropical forests, causing deforestation and biodiversity loss, which contribute to climate change at an uncontrollable pace. Oil palm agroforestry systems (AFSs), one of the strategies of regenerative agriculture, have proven to reverse the unfavorable effects of the oil palm monoculture systems. A sustainable means of soil fertilization and irrigation must be explored to improve the feasibility of oil palm AFSs. This study evaluates the impact of the application of oil palm ash and brackish irrigation on cherry tomato production. The experiment was conducted in a hydroponic system using a 2*4 factorial experimental design to investigate the impact of the application of four fertilizer treatments namely T1: oil palm ash; T2: plant-based compost; T3: oil palm ash and plant-based compost (1:1); and T4: no fertilizer treatment, only irrigated with A&B Nutrient Solution (NS) as the control treatment and two water salinity levels of fresh and brackish water on cherry tomato fruit yield, cherry tomato fruit nutrient concentration levels and the total organic matter (TOM) and total organic carbon (TOC) of the soil used in this study for the cultivation of cherry tomatoes. For freshwater, T3 recorded an average fruit yield of 33.016 tons/ha compared to the average yield of the control treatment of 35.775 tons/ha with no significant difference between them. For brackish water, compared to the average fruit yield of the control treatment of 27.802 tons/ha, T3 noted an average fruit yield of 27.330 tons/ha with no significant difference. In the cherry tomato samples that were irrigated with fresh water, the ones from T3 were higher than the control treatment in K, Ca, Zn, Mg, and Na while with brackish water, T3’s cherry tomato samples were higher in N, K, Ca, Fe, Mn, Zn, Cu, Mg and Na when compared to the control treatment. In T1, the soil that was irrigated with freshwater exhibited the only increase of about 25.57% in TOM and TOC with a p-value of 0.000 whereas the soil that was irrigated with brackish water displayed the least reduction of about 17.41% with a p-value of 0.000. Both the TOM and TOC significantly decreased in the soil samples that were irrigated with water from both salinity levels in T2, T3, and the control treatment. Subsequent studies should be conducted to determine the appropriate application rate of oil palm ash for cherry tomatoes in diverse water salinity levels, evaluate the application of oil palm ash on other crops irrigated with higher water salinity levels, investigate the impact of the combination of oil palm ash and plant-based compost on other crops in brackish water irrigation. Our findings suggest that the use of oil palm ash and brackish water is a sustainable means of soil fertilization and irrigation, that will enable oil farmers to transition oil palm monoculture to oil palm AFSs.